Improving the Learning Outcomes of Third-Grade Students at Bangsal 3 Elementary School Through the Implementation of the Problem-Based Learning Model in the Science and Social Studies Subject - Anisha Intan Wahyu Putri (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction to The Problem: The low learning outcomes in the IPAS subject (Natural and Social Sciences) among third-grade students at SD Negeri Bangsal 3 served as the basis for this study. Initial assessment showed that only 10 out of 28 students (35.7%) met the Minimum Mastery Criteria (KKM). Purpose: This research aims to improve students' academic achievement through the implementation of the Problem-Based Learning (PBL) model, which encourages active engagement and contextual problem solving. Design/methods/approach: The study employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles during the second semester of the 2024/2025 academic year. The participants were 28 third-grade students. Data collection methods included observation, achievement tests, and documentation, which were analyzed using descriptive quantitative analysis. Findings: The findings revealed a significant improvement in learning outcomes: in Cycle I, the number of students achieving mastery increased to 17 (60.7%), and in Cycle II, it rose to 25 students (89.3%). Research implications/limitations: While the model yielded positive results, the study's limitations included the short implementation period and individual student differences. Originality/value: These findings highlight the originality and relevance of applying the PBL model in primary IPAS education, particularly for topics that require conceptual understanding and teamwork. The research provides valuable insights for primary school teachers in adopting adaptive, contextual, and student-centered learning strategies. It is recommended that the PBL model be further applied to other IPAS topics and combined with digital media for enhanced effectiveness.